A pharmacodynamic investigation into the efficacy of osteoprotegerin during aseptic inflammation - Curl Linda; Barker Christopher; Dreyer Craig; Sampson Wayne (Sciendo, 2012)
Background: Osteoprotegerin (OPG), as an osteoclast antagonist, limits mineralised tissue resorption under physiological conditions. Previous work investigating OPG in a rat periodontal ligament (PDL) ankylosis model found no inhibitory effect on osteoclasts when OPG was administered at a dosage of 2.5mg/kg.1,2